2004
DOI: 10.1097/01.sla.0000124291.09032.bf
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Vacuum-Assisted Fascial Closure After Open Abdomen

Abstract: The use of VAFC under a carefully defined protocol has resulted in significantly higher fascial closure rates, obviating the need for subsequent hernia repair in most patients. The utility of this technique is not limited to the early postoperative period, but it can be successful as much as 3 to 4 weeks after initial operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(165 citation statements)
references
References 20 publications
2
144
0
19
Order By: Relevance
“…The review of 18 series with overall 1395 patients managed by OA and V.A.C. revealed a mean rate of EAFs 6.1% (Table 2), (4,8,14,17,19,20,(26)(27)(28)(29)31,32,(36)(37)(38)42,45,47), which is comparable to 7.2% in our series.…”
Section: Discussionsupporting
confidence: 56%
“…The review of 18 series with overall 1395 patients managed by OA and V.A.C. revealed a mean rate of EAFs 6.1% (Table 2), (4,8,14,17,19,20,(26)(27)(28)(29)31,32,(36)(37)(38)42,45,47), which is comparable to 7.2% in our series.…”
Section: Discussionsupporting
confidence: 56%
“…The introduction of negative pressure therapy with the home-made so called VAC-PAC method was pioneered in Philadelphia [37], and was later developed further into the Abdominal V.A.C system, a commercially available dressing (KCI, San Antonia, TX, USA). This system, also labeled VAWC was associated with high closure rates in cohorts of mostly young trauma victims from the USA [27,38]. Many researchers who started to use the VAWC system on emergency surgical care patients, often elderly patients suffering from pancreatitis, septic abdomen or vascular catastrophes, found that this system alone was not sufficient to be able to close the abdomen after the often longer periods of treatment with open abdomen that is required in such patients.…”
Section: Combining Fascial Approximation and Npt -A Solution?mentioning
confidence: 99%
“…Barker in 2000 [26] reported closure rates of 55% using this technique; the enteric fistula rate was 4%. In 2004, Miller et al [27] published a report to examine the success of vacuum-assisted fascial closure (VAFC) under a carefully applied protocol in abdominal closure after open abdomen. It concluded that the use of VAFC under a carefully defined protocol has resulted in significantly higher fascial closure rates, obviating the need for subsequent hernia repair in most patients.…”
Section: Temporary Abdominal Closurementioning
confidence: 99%
“…After that, the deliberately created ventral hernia is repaired 6-12 mo later. The above situation has been changed considerably with the introduction of vacuum application and biological prosthetic material [1][2][3][4][5] . Until recently, the practice was to discharge patients with an open fascia and partially closed skin.…”
Section: To the Editormentioning
confidence: 99%
“…It is reported that by using vacuum methods, fascial defects are reduced sufficiently to be closed [1][2][3][4] . It is also reported that in cases where closure is inadequate, by using acellular dermis, patients can be sent home without a fascial defect [5] .…”
Section: To the Editormentioning
confidence: 99%